Halal Production and Efficiency in Realizing the Value of Economic Blessings: A Study of the Islamic Economics Literature: Produksi Halal dan Efisiensi dalam Mewujudkan Nilai Keberkahan Ekonomi Studi Pustaka Ekonomi Syariah - Surasa, Danil; Rokhlinasari, Sri; Haerisma, Alvien Septian (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Islamic economics emphasizes that economic performance is evaluated not only by profit and efficiency but also by ethical and spiritual values. Specific Background: Halal production extends beyond legal compliance toward moral responsibility, while sharia efficiency integrates optimal resource use with justice, sustainability, and maqāṣid al-sharī‘ah. Knowledge Gap: Prior studies largely examine halal production, efficiency, and economic blessings separately, leaving their conceptual interrelationship insufficiently articulated in a systematic framework. Aims: This study analyzes the conceptual linkage between halal production and sharia efficiency in realizing economic blessings within Islamic economic literature. Results: The findings indicate that halal production promotes the formation of sharia efficiency encompassing process, distribution, and value dimensions. Sharia efficiency functions as a mediating construct connecting halal production to economic blessings, reflected in business sustainability, equitable benefit distribution, and improved welfare. The three constructs exhibit an integrative and mutually reinforcing relationship within a maqāṣid-based framework. Novelty: The study proposes a conceptual model positioning sharia efficiency as the central linkage that operationalizes the relationship between halal production and economic blessings. Implications: This integrative perspective provides a foundation for advancing Islamic economic theory and offers a conceptual basis for developing value-oriented halal industry practices and future empirical research. Highlights• Demonstrates integrative linkage among three core constructs within a maqāṣid framework• Identifies mediating role connecting production principles and welfare outcomes• Establishes value-oriented optimization as a basis for sustainable economic welfare KeywordsHalal Production; Sharia Efficiency; Economic Blessings; Maqasid; Sustainability